The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7se00258k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of esterification of 10-undecenoic and ricinoleic acids with near-critical and supercritical methanol

Abstract: FAMEs were synthesized from two different carboxylic acids using a green pathway and a new mechanistic kinetic model was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Using the supercritical methods, the reported biodiesel yields vary from 95.22 to 96.5% and even if such methods produce high yields of biodiesel, their energy demand is often high. The reaction conditions for supercritical methods often require higher amount of alcohol versus oil for the alcoholysis [30]. At the same time, the process conditions include higher temperatures and pressures but shorter reaction times [28,57].…”
Section: Catalyst Test and Doe Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the supercritical methods, the reported biodiesel yields vary from 95.22 to 96.5% and even if such methods produce high yields of biodiesel, their energy demand is often high. The reaction conditions for supercritical methods often require higher amount of alcohol versus oil for the alcoholysis [30]. At the same time, the process conditions include higher temperatures and pressures but shorter reaction times [28,57].…”
Section: Catalyst Test and Doe Resultsmentioning
confidence: 99%
“…Biodiesel production based on Ricinus oil has been studied by different reaction systems; i.e. homogeneous and heterogeneous catalysts, supercritical methods and enzymatic methods [22,[26][27][28][29][30]. Previously published work shows the suitability and the stability of the mayenite structure that offers the macro-porosity needed for the triglyceride and methanol molecules to interact at the catalyst active sites [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This result justifies Le Chartelier's principle. It is worth knowing that the operating costs may increase with a high amount of alcohol because of the amount of alcohol that needs to be evaporated after the reaction, which demands a higher heat load 147 …”
Section: Chemical Modification Of Oils For Biolubricants Synthesismentioning
confidence: 99%
“…153 Furthermore, most acid and base-catalysed reactions show higher FAME yields at longer reaction times. In a kinetic study of esterification reaction of 10-undecenoic ricinoleic acids and supercritical methanol, Narayan et al, 147 reported more than 80% conversion at different molar ratios (ie, 1:1;2:1;5:1, and 40:1). For both reactions (ie, methanol and 10-undecenoic acid and methanol and ricinoleic acid), the conversion of the reactions increased with time at respective temperatures of 523 K, 573 K, 623 K, and 673 K. For the second-stage process, a similar relationship is witnessed at a longer period of the process.…”
Section: Reaction Temperature and Reaction Timementioning
confidence: 99%